The Effect Of Earnings Management And Ownership Structure On Stock Returns: A Case Study Of The Pharmacy And Health Sub-Sectors Listed On The IDX In 2021-2023 - Adinda Sefa Saimeyna; Shiwi Angelica Cindiyasari (Jurnal Ekonomi, 2024)
Earnings management does not consistently impact stock returns, with some studies supporting its influence and others disputing it. This inconsistency creates challenges for investors seeking to make optimal investment decisions. This study aims to investigate and analyze the impact of earnings management and ownership structure on stock returns. The research uses a quantitative approach, relying on secondary data sourced from company annual financial reports. The population and sample comprise the financial reports of pharmaceutical and healthcare sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. A total of 10 companies in these sub-sectors were included in the sample, selected using purposive sampling. Panel data regression analysis was employed to analyze the data. The study’s findings indicate that, individually, earnings management does not significantly impact stock returns, nor does ownership structure. Nonetheless, when taken into account jointly, ownership structure and profits management significantly impact stock returns in the pharmaceutical and health subsectors listed on the IDX between 2021 and 2023.